Synthesis of Biodiesel from Used Frying Oil Using Modified Banana Peel Waste as A Heterogeneous Catalyst - Nur Suhaida, Roslan; Lee, Yong Siang; Noor Yahida, Yahya; Noor Amirah, Abdul Halim (Universiti Teknologi PETRONAS, 2023)
In this study, biodiesel was synthesised from a transesterification reaction of used frying oil (UFO) catalysed by modified banana peel waste (Modified-BPW). The catalyst properties were characterised using Fourier Transform Infrared Spectrometer (FTIR) and Scanning Electron Microscopy (SEM) analyses. The reaction parameters were varied to evaluate the optimal reaction parameters that could influence the biodiesel yield, such as methanol to oil molar ratio, catalyst loading amount and water content presence in the UFO at a fixed reaction time of 2 hours and a reaction temperature of 65°C. The catalytic activity resulted in the reaction condition of 12:1 of methanol to oil molar ratio, 1 wt.% of catalyst dosage and 0.5 wt.% water content in UFO, obtaining the highest biodiesel yield of 88.7%. The results indicated that the Modified-BPW could be a promising catalyst for biodiesel synthesis from UFO.